2016
DOI: 10.1007/s11010-016-2742-x
|View full text |Cite
|
Sign up to set email alerts
|

Sulfasalazine intensifies temozolomide cytotoxicity in human glioblastoma cells

Abstract: Temozolomide (TMZ) is an alkylating agent used to treat glioblastoma. This tumor type synthesizes the antioxidant glutathione through system X c (-) , which is inhibited by sulfasalazine (SAS). We exposed A172 and T98G human glioblastoma cells to a presumably clinically relevant concentration of TMZ (25 µM) and/or 0.5 mM SAS for 1, 3, or 5 days and assessed cell viability. For both cell lines, TMZ alone did not alter viability at any time point, while the coadministration of TMZ and SAS significantly reduced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…An increased antitumor effect was observed in the combination group compared with the single treatment group []. Silencing of NrF2 (nuclear factor erythroid 2‐related factor 2) and inhibition of glutathione greatly enhanced cell death with TMZ treatment both in vitro and in vivo [, ].…”
Section: Introductionmentioning
confidence: 99%
“…An increased antitumor effect was observed in the combination group compared with the single treatment group []. Silencing of NrF2 (nuclear factor erythroid 2‐related factor 2) and inhibition of glutathione greatly enhanced cell death with TMZ treatment both in vitro and in vivo [, ].…”
Section: Introductionmentioning
confidence: 99%
“…It is also encouraging that talampanel did not increase the hematological side Glioma cell-derived xCT is, at least, partly responsible for promoting cortical hyperexcitability, brain edema, and neuronal cell death [25,[86][87][88]. Further, pharmacological antagonism with the FDA-approved compound sulfasalazine diminishes cortical hyperexcitability and augments temozolomide efficacy against glioma cells in vitro [86,89]. Unfortunately, available clinical evidence suggests that sulfasalazine also augments the hematological side effects of radiation + temozolomide [90].…”
Section: Pharmacological Targeting Of Aberrant Glutamatergic Action Imentioning
confidence: 99%
“…However, the development of TMZ resistance promotes the survival of glioma cells and leads to poor prognosis of patients. To overcome TMZ resistance, studies have found that metformin or sulfasalazine could enhance the cytotoxicity of TMZ in glioblastoma cells ( Ignarro et al, 2016 ). Mechanistically, DNA repair systems, including DNA mismatch repair (MMR) ( Perazzoli et al, 2015 ) and base excision repair (BER) ( Tang et al, 2011 ), play important roles in the mechanisms of TMZ resistance.…”
Section: Introductionmentioning
confidence: 99%